Analisis Beban Pendinginan di Ruang Kelas F212 Institut Teknologi Sumatera - Manurung, Daniel; Furkhan, M. Aulia; G., Gita Christo; Alfian, Devia Gahana Cindi; Silitonga, Dicky J.; Carlodinho, Samuel; Khaira, M. Irsyad Bin Iskandar (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2025)
Cooling load analysis in the classroom is carried out to support a comfortable learning process. Determining the cooling load is the foundation for planning an air conditioning system for a room. From the results of this determination, the capacity of the AC machine device used can be estimated. The method used in this solution is observation in the room, consisting of direct observation, measurement, and data recording. After obtaining all the data and calculating all possible heat dissipation factors, the total cooling load value in the room is 8584.34 W. The cooling capacity of the AC specifications in the room is 10040 W. Based on the results obtained, the total cooling load is lower than the cooling capacity of the AC in the room. So that the AC capacity in the room can provide comfort for the load in the room.